2012
DOI: 10.1021/jp3017198
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization ofcis-1-(3-Methyl-2-naphthyl)-2-phenylethene in Glassy Methylcyclohexane at 77 K

Abstract: The cis-trans photoisomerizations of cis-1-(3-methyl-2-naphthyl)-2-phenylethene (c-3-MPE) was studied in methylcyclohexane (MCH) glass at 77 K. The fluorescence spectra of c- and t-3-MPE are excitation wavelength (λ(exc)) independent because the steric requirement of the methyl group restricts the conformational space of each isomer to a single conformer. Photocyclization, the dominant reaction pathway of c-3-MPE in solution, is entirely suppressed in MCH glass at 77 K. The only reaction on 313 nm irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Results for Pre are summarized in Table . The shortcomings of DFT B3LYP calculations to accurately predict relative hydrocarbon energy differences have been highlighted in several recent publications. , In our experience, very good agreement between experimental results and DFT B3LYP theoretical predictions was realized for conformer and isomer energetics of a simple butadiene, diphenylpolyenes, and 1,2-diarylethenes ,, in their S 0 and T 1 states. The calculations predict a plethora of Pre and Tachy conformers in close energetic proximity.…”
Section: Resultssupporting
confidence: 58%
“…Results for Pre are summarized in Table . The shortcomings of DFT B3LYP calculations to accurately predict relative hydrocarbon energy differences have been highlighted in several recent publications. , In our experience, very good agreement between experimental results and DFT B3LYP theoretical predictions was realized for conformer and isomer energetics of a simple butadiene, diphenylpolyenes, and 1,2-diarylethenes ,, in their S 0 and T 1 states. The calculations predict a plethora of Pre and Tachy conformers in close energetic proximity.…”
Section: Resultssupporting
confidence: 58%
“…Formation of an unstable trans conformer starting from the o ‐tolyl analog of c ‐NPE ( c ‐NTE, Scheme , in EPA glass at 77 K was thought to confirm the benzylic HT pathway . On the basis of the known t ‐NPE A and t ‐NPE B absorption spectra , we pointed out that the correct assignment of the thermal relaxation of the photoproduct of c ‐NTE in EPA glass at 77 K is t ‐NTE A → t ‐NTE B (Scheme , right side). Therefore, depending on the correct structural assignment to the c ‐NTE conformer that exists in EPA glass, either the HT or the OBT mechanism will account for the results.…”
Section: Introductionmentioning
confidence: 93%
“…We showed that at 77 K in glassy MCH the photoisomerizations of cis ‐1‐(2‐naphthyl)‐2‐phenylethene ( c ‐NPE, Scheme , that exists mainly as the B conformer and cis ‐1‐(3‐methyl‐2‐naphthyl)‐2‐phenylethene ( c ‐3‐MPE) that should exist as the A conformer (Scheme , bottom left, proceed as shown by the OBT labeled pathways c ‐NPE B → t ‐NPE B and c ‐3‐MPE A → t ‐MPE A in Scheme . However, our conclusion that no HT is involved in those reactions was dismissed because HT photoisomerization about the benzylic CH would lead to the same result .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoisomerization in linear polyenes is highly regioselective and is much influenced by substitutent, polarity of the medium [28][29][30][31][32][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and dipolar nature of the excited state [74][75][76][77][78]. Various mechanistic models have been proposed to understand the photoisomerization process of retinyl and related polyenes.…”
Section: Cistrans-photoisomerization Of Diphenylpolyenesmentioning
confidence: 99%